2022
DOI: 10.3389/fendo.2022.885507
|View full text |Cite
|
Sign up to set email alerts
|

The Dibenzyl Isoquinoline Alkaloid Berbamine Ameliorates Osteoporosis by Inhibiting Bone Resorption

Abstract: Postmenopausal osteoporosis (PMOP) is a kind of primary osteoporosis that is characterized by decreased bone density and strength. Berbamine is a nonbasic quaternary benzylisoquinoline plant alkaloid that has been widely used in the clinic to treat leukopenia in China. We found that berbamine inhibited RANKL-induced osteoclastogenesis of bone marrow-derived macrophages (BMMs) in vitro, which mainly occurred in the middle phase and late phase. The gene and protein expression levels of osteoclast-related molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…In previous studies, we have identified a number of small molecule drugs that could alleviate OVX-induced bone loss in mice by preventing pre-OC fusion or inhibiting osteoclast differentiation [ 39 , [52] , [53] , [54] ]. In the course of these studies, we found that the susceptibility of cells to certain drugs changes during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we have identified a number of small molecule drugs that could alleviate OVX-induced bone loss in mice by preventing pre-OC fusion or inhibiting osteoclast differentiation [ 39 , [52] , [53] , [54] ]. In the course of these studies, we found that the susceptibility of cells to certain drugs changes during osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…BMDMs were isolated from wild-type or SLC7A11 −/− mice as previously described [ 39 ]. Briefly, 4-week-old C57BL/6J mice were dissected under Zoletil 50 (50 mg/kg) anaesthesia, and the tibiae and femora were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of these drugs will inevitably bring certain side effects. For example, bisphosphonates can cause hypocalcemia, osteonecrosis of the jaw, and atrial fibrillation ( 106 , 107 ). Denosumab, a human anti-RANKL antibody, potently blocks the interaction between RANK and its ligands to inhibit bone resorption, but long-term use can lead to infection, rash, and atypical femoral fractures ( 108 , 109 ).…”
Section: Other Forms Of Osteolysis Mediated By Macrophages/osteoclastsmentioning
confidence: 99%
“…It also has the effects of beneficial Qi, invigorating the spleen, and reducing edema. The active ingredients in FJ are mainly dibenzyl isoquinoline alkaloids, such as tetrandrine, fangchinoline, and rocinoline, which have analgesic, antitumor, antifibrotic, and anti-inflammatory effects [ 7 , 8 ]. Our previous study found that N-methylfangchinoline, fangchinoline, tetrandrine, tetrandrine-M3, and tetrandrine-M4 have the same structure, which can cooperatively improve kidney injury [ 9 ].…”
Section: Introductionmentioning
confidence: 99%